MICOLLAC 2009 - Sunday Star, (2008)
UNIVERSTI Putra Malaysia's Faculty of Modern Languages and Communication is organising the sixth Malaysia International Conference on Languages Literatures and Cultures (MICOLLAC) at Putrajaya Marriott Hotel from April 28 to 30 next year The theme is "Universals Distinctions and Cross disciplinary perspectives".